Penggunaan Pembelajaran Kooperatif untuk Meningkatkan Pembelajaran Bahasa Arab bagi Non Penutur Asli - nur faiz (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Raden Fatah, 2021)
This research aims to present the role of cooperative education in promoting Arabic language skills for non-native speakers, what is its status, how its procedures, and its results. The researcher uses the qualitative approach through the desk study with the content analysis technique. The primary data sources are collaborative learning research published in Google Cendekia Five years ago. The results of this research indicate that the cooperative learning is more applied in the skill of reading, speaking, and writing. And that its procedures or steps use on cooperation and learning centered on students. And its results are upgrade all Arabic language skills and workers that influence the success of skills training. Keyword : Cooperative Learning, Arabic Language, and Language Skill